Mechanisms of Action for Antimicrobial Peptides With Antibacterial and Antibiofilm Functions - Raheem, Nigare; Straus, Suzana K. (Frontiers in Microbiology, 2019)
The antibiotic crisis has led to a pressing need for alternatives such as antimicrobial peptides (AMPs). Recent work has shown that these molecules have great potential not only as antimicrobials, but also as antibiofilm agents, immune modulators, anti-cancer agents and anti-inflammatories. A better understanding of the mechanism of action (MOA) of AMPs is an important part of the discovery of more potent and less toxic AMPs. Many models and techniques have been utilized to describe the MOA. This review will examine how biological assays and biophysical methods can be utilized in the context of the multiple biological functions of AMPs.